Re-visiting the diastereoselectivity of organocatalytic conjugate addition of 2-trimethylsiloxyfuran to trans-crotonaldehyde. (25th May 2021) - Li, Liubo; El Khoury, Anton; Clement, Brennan O.; Harran, Patrick G.
Graphical abstract: Highlights: Conjugate addition sof 2-siloxyfuran to crotonaldehyde affords isomeric butenolides. Chiral imidazolidinone catalysis affords the ' anti ' isomer with moderate selectivity. Chiral prolinol catalysis generates the ' syn ' isomer with high dr and ee . Abstract: We describe the re-assignment of configuration previously ascribed to product diastereomers resultant from imidazolidinone-catalyzed conjugate addition of 2-trimethylsiloxyfuran to trans -crotonaldehyde. A modified procedure that uses a diphenylprolinol catalyst was subsequently developed to selectively provide the ' syn ' diastereomeric product in high enantiomeric excess on decagram scales.